Energy balance movement schemes for maximising network lifetime in WSRNs. (2017) - Chang, Chao-Tsun; Kuo, Chin-Hwa; Hsiao, Chih-Yao
Wireless sensor and robot network (WSRN) is composed of a set of sensors and robots. The mobility of robots has been proved to be quite useful in prolonging the network lifetime. However, mobility is the major energy consumption of robot. Thus, the mobility of robots requires intelligent control in order to efficiently complete appointed tasks. Compared with lightweight sensors, using robots to transmit heavy data (such as audio or video data) is more appropriate. Therefore, a communication path, which is composed of robots between the base station (BS) and the event point, should be maintained. In this paper, three movement schemes called greedy back-up (GB), stretched back-up path (SBP) and back-up path regression (BPR) approaches, are proposed, aiming to construct the data delivery path while maximising the network lifetime. Experimental results show that the proposed schemes outperform the compared MH-MDRM-CP approach in terms of network lifetime and moving distance.